Gene therapy in Duchenne muscular dystrophy: Identifying and preparing for the challenges ahead - Heslop, Emma (Neuromuscul Disord, 2021)
• Despite the burden of gene therapy trials for DMD patients there is great enthusiasm. • Collaborating with relevant bodies (pharmacy) at an early stage can accelerate progress. • A hub and spoke model may be an option for delivering clinical trials and follow up care.